ANALYSIS OF LNCRNAS AND CIRCRNAS IN GLYCINE MAX UNDER DROUGHT AND SALINE-ALKALINE STRESSES - Y. Dong; Y. Wang; G. Wang; N. Ahamd; L. Wang; Y. Wang; X. Zhang; X. Li; H. Li (Journal of Animal and Plant Sciences, 2022)
Long noncoding-RNAs (LncRNAs) and circular RNAs (circRNAs) are the major types of noncoding RNAs (ncRNAs) known to be involved during diverse biological processes in eukaryotes. However, less attention has been given to the identification, overall characteristics and expression analysis of LncRNAs and circRNAs under abiotic stresses in plants.. In our study, strand-specific RNA-seq data revealed the identification of a total 2,020 lncRNAs, including 1,979 known and 41 novel ones, and 830 circRNAs in soybean. Overall, 118 and 47 lncRNAs showed significant changes in expression levels under drought stress and saline-alkaline stress, respectively. In addition, soybean lncRNAs indicated diverse expression patterns suggesting a positive correlation with many biological processes including photosynthesis during stress responses by regulating gene expression in a cis-/trans-actingmanner. Our findings further indicated that transcriptional biosynthesis pathways and RNA transcriptional regulation were positively regulated during stress conditions. Furthermore, the back-splicing sites of circRNAs were also confirmed. Collectively, our study identified a group of stress-responsive lncRNAs and circRNAs in soybean, highlighting their potential contributions to abiotic stress responses, which pave the way for future functional studies.
Keywords: Strand-specific RNA sequencing; Stress response; lncRNA; circRNA; Expression pattern